1999
DOI: 10.1177/002215549904700809
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Distribution of 36-kD Microfibril-associated Glycoprotein (MAGP-36) in Human and Bovine Tissues

Abstract: SUMMARYWe observed the ultrastructural distribution of MAGP-36 by immunoelectron microscopy in human and bovine tissues. MAGP-36 was present in microfibrils associated with tropoelastin in skin, aorta, and spleen. It was not detected in microfibrils from the ocular zonule and kidney mesangium that were not associated with tropoelastin. In skin, MAGP-36 was present in both early immature elastic fibers and mature elastic fibers. In mature elastic fibers, MAGP-36 was localized around amorphous elastic cores at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…MFAP 4 is a 29-kDa elastin-binding protein and plays a role in elastogenesis. 37 Furthermore, MFAP 4 has high sequence homology to the aortic aneurysm-associated protein-40, which has been found in human abdominal aortic aneurysm. 38 Although not much is known about MFAP 4, there are indications that it might play an important role in aneurysm formation.…”
Section: Discussionmentioning
confidence: 98%
“…MFAP 4 is a 29-kDa elastin-binding protein and plays a role in elastogenesis. 37 Furthermore, MFAP 4 has high sequence homology to the aortic aneurysm-associated protein-40, which has been found in human abdominal aortic aneurysm. 38 Although not much is known about MFAP 4, there are indications that it might play an important role in aneurysm formation.…”
Section: Discussionmentioning
confidence: 98%
“…Human MFAP4 has been localized to elastic fibers in a variety of elastic tissues, including aorta (23), skin (24), and lung (23,25). Immunogold electron microscopy studies have shown that MFAP4 localizes to elastin-associated microfibrils but not microfibrils away from the elastin bundle (24). Together, these observations suggest that MFAP4 may contribute to the elastic fiber assembly and/or maintenance.…”
Section: Mfap4 (Microfibrillar-associated Protein 4)mentioning
confidence: 91%
“…MAGP-36 has been found to bind elastin and collagen in a calcium-dependent manner and to co-localize with elastin microfibrils (21,22). Human MFAP4 has been localized to elastic fibers in a variety of elastic tissues, including aorta (23), skin (24), and lung (23,25). Immunogold electron microscopy studies have shown that MFAP4 localizes to elastin-associated microfibrils but not microfibrils away from the elastin bundle (24).…”
Section: Mfap4 (Microfibrillar-associated Protein 4)mentioning
confidence: 99%
“…4 MFAP4, known as 36-kDa microfibril-associated glycoprotein (MAGP36) 5 in other species, was first identified as a protein with a resemblance to tenascin in its amino acid composition and localization to the ECM in arteries. [6][7][8][9][10] MAGP36 is known to interact directly with ECM fibers, including elastin, collagen, and calvasculin. [6][7][8]11 Moreover, MAGP36 was demonstrated to bind integrin receptors on human aortic SMCs in an RGD-dependent manner.…”
mentioning
confidence: 99%